Fishing simulation experiments for predicting the effects of purse-seine capture on sardine (Sardina pilchardus) - Marçalo, Ana (2016)
To study the impact of purse-seine fishing on deliberately released sardine, two laboratory experiments were performed to explore the effect of net confinement for 10, 20, 40, and 60 min at 18 and 238 degrees C. A third experiment considered two levels of fish density while confined for 20 and 40 min at 16 degrees C. Analysis of cortisol and haematocrit demonstrated that stress immediately after simulated fishing was milder than in commercial fishing and did not correlate with observed delayed mortality. Scale loss was related to the probability of dying (mean values of 16.3 and 2% for dead fish and survivors, respectively), and fin erosion was a long-term stress response observed in both dead and surviving fish. Time of confinement was an important stressor, with survival rates decreasing significantly with increasing periods in the net, and temperature having an additional negative effect. Density effects were less conclusive, but there was some indication that survival correlated with biological condition (heavier fish were more likely to survive). It seems that delayed mortality after release can be substantial, although death is not certain and appropriately modified fishing operations and favourable environmental conditions may enhance the probability of sardine survival.